Geopolitics an introductory reader - Dittmer, Jason; Sharp, Joanne (London Routledge, 2014)
"Description Drawing both on academic and political material, this book introduces readers to the concept of geopolitics, from the first usage of the term to its more recent reconceptualisations. The concept of geopolitics is introduced through four thematic sections - imperial geopolitics, cold war geopolitics, post-cold war geopolitics and reconceptualising geopolitics - which establish the foundations of geopolitics while also introducing readers to the continuing significance of the concept in the 21st century. Each section includes key papers from a range of diverse but leading authors such as Said, Agnew, Dalby, O Tuathail, Gregory, Barnett and Kaplan, and is accompanied by a critical introduction by the editors to guide the reader through the material"--Publisher.
Includes bibliographical references and index.
Keywords: Geopolitics